Design and development of aerogel-filled sandwich composite structures - Xu, Kaibin. (2011)
Silica aerogel is an extremely lightweight material with an amazing heat insulation property. These properties present opportunities to develop lightweight and thermally insulating composite materials. The aerogel-filled sandwich composite structure can then be used in any applications that require shielding against undesired heat gain or unwanted heat loss. Possible applications of these composites include aircraft cabins, vehicle engines, thermal shelters, and building insulations. Acoustic insulation and moisture barrier properties can also be generated in such composites.